1998
DOI: 10.1212/wnl.50.1.279
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk factors for Parkinson's disease in an urban multiethnic community

Abstract: Environmental risk factors were examined using univariate and multivariate unconditional logistic regression models in 89 nondemented patients with Parkinson's disease (PD) and 188 control subjects in a multiethnic urban community. Rural living, area farming, and drinking well water were associated with PD only in African-Americans. In Hispanics, area farming was protective, whereas drinking unfiltered water was a risk factor for PD. Consideration of ethnic and cultural origin may add to the epidemiologic stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 4 publications
0
28
0
Order By: Relevance
“…Consistent findings of epidemiological studies associate between increased disease risk and such environmental factors as rural residence [Morano et al, 1994;Liou et al, 1997, Marder et al, 1998], farming [Semchuk et al, 1993;Liou et al, 1997;Gorell et al, 1998;Fall et al, 1999], the drinking of water from wells [Morano et al, 1994;Liou et al, 1997, Marder et al, 1998], and exposure to agricultural chemicals, pesticides, and/or herbicides [Semchuk et al, 1992;Semchuk et al, 1993;Liou et al, 1997;Gorell et al, 1998;Fall et al, 1999;Vanacore et al, 2002]. Recently, several models have been elaborated in which exposure of animals to various pesticide and herbicides has been used to induce Parkinsonism [Uversky, 2004, for review].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent findings of epidemiological studies associate between increased disease risk and such environmental factors as rural residence [Morano et al, 1994;Liou et al, 1997, Marder et al, 1998], farming [Semchuk et al, 1993;Liou et al, 1997;Gorell et al, 1998;Fall et al, 1999], the drinking of water from wells [Morano et al, 1994;Liou et al, 1997, Marder et al, 1998], and exposure to agricultural chemicals, pesticides, and/or herbicides [Semchuk et al, 1992;Semchuk et al, 1993;Liou et al, 1997;Gorell et al, 1998;Fall et al, 1999;Vanacore et al, 2002]. Recently, several models have been elaborated in which exposure of animals to various pesticide and herbicides has been used to induce Parkinsonism [Uversky, 2004, for review].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have, to varying extents, implicated exposures such as pesticides, solvents, neurotoxic metals, well-water consumption, and rural residency 2,3 . Of these exposures, pesticides have most frequently returned a positive association, though not consistently.…”
Section: Introductionmentioning
confidence: 99%
“…A case-control study conducted in New York found that PD risk increases with education level (Marder et al, 1998). In contrast, Taylor et al (1999) showed that a high education level was protective factor in PD.…”
Section: Pd-related Factorsmentioning
confidence: 99%